Soil bacterial community structure at different plant maturity stages in an annual grass–legume production system - Xie, Yixiao; Liu, Wen; Li, Ping; Bai, Shiqie; Li, Daxu; Zhang, Lixia; Sun, Hong; Zheng, Yulong; Cheng, Qiming; Wang, Chunmei; Du, Ermei; Gou, Wenlong (Frontiers in Sustainable Food Systems, 2023)
Introduction To infer changes in soil function and thus determine appropriate agronomic management practices, this study evaluated the effects of plant maturity stage on root characteristics, soil chemical and enzymatic properties, and soil bacterial community composition in an annual grass–legume production system. Methods Annual ryegrass or rye was sown in combination with one of three legume species at a legume ratio of 50%. Eighteen plots (six plant combinations, three replicates per combination, 20 m × 25 m plots) were tilled to a depth of 20 cm after mowing. Soil samples from each plot were collected on four dates as the plants matured: January 4 (H1), March 14 (H2), April 21 (H3), and May 19 (H4). Bacterial community structures were characterized via 16S rRNA high-throught sequencing and the bio-informatics methods were used to evaluate the structural characteristics of soil bacteria. Results The most abundant root growth was observed at the H3 stage. No significant differences in organic matter, alkali-hydrolyzable nitrogen, available phosphorus, and available potassium contents (p > 0.05) were observed on any sampling date. Soil collected at the H3 stage exhibited lower acid protease and urease activities (p < 0.05) and higher nitrate reductase activity (p < 0.05). The structure of the microbial community at stage H3 differed markedly from that at other stages, as evidenced by a higher abundance of Proteobacteria, Bacteroidetes, Acidobacteria, and Verrucomicrobia (p < 0.05) and a lower abundance of Actinobacteria, Cyanobacteria, and Planctomycetes (p < 0.05). At the class level, the relative abundances of Sphingobacteria, Betaproteobacteria, and Gammaproteobacteria in soil was higher at H3 stage than those of other stages (p < 0.05). The order level for Sphingomonadales, Sphingobacteriales, and Burkholderiales and at the family level for Chitinophagaceae and Sphingomonadaceae showed the same trend toward higher. Conclusion Nutrient cycling in the soil was slowed at the H3 stage, and the loss of nitrogen would also be greater. Measures may need to be taken to improve the nitrogen fertilizer utilization efficiency to reduce denitrification and nitrous oxide production at this stage (the booting stage of grasses and budding stage of legumes).